Threshold effects of financial stress on monetary policy rules: A panel data analysis - Danvee Floro; Björn Van Roye (European Central Bank (ECB), 2017)
This study tests for the state-dependent response of monetary policy to increases in overall financial stress and financial sector-specific stress across a panel of advanced and emerging economy central banks. We use a factor-augmented dynamic panel threshold regression model with (estimated) common components to deal with crosssectional dependence. We find strong evidence of state-dependence in the response of monetary policy to financial sector-specific stress for advanced economy central banks, as they pursue aggressive monetary policy loosening in response to stock market and banking stress only in times of high financial market volatility. By comparison, evidence of threshold effects of financial stress is generally weak for emerging market central banks.
Keywords: E31; E44; E52; E58; C23; C24; 330; financial stress; monetary policy; threshold panel regression; cross-section dependence